Generation Algorithms for Thévenin and Norton Equivalent Circuits - Mihaela Grib; Ioana-Gabriela Sirbu; Lucian Mandache; Marilena Stanculescu; Mihai Iordache; Lavinia Bobaru; Dragos Niculae (Energies)
The growing complexity of electrical systems requires advanced analysis tools to optimize the design time and resources. While many circuit simulators exist, they often lack the flexibility needed for real-world applications. In this context, our paper develops practical approaches to building Thévenin and Norton equivalent diagrams by means of modern software facilities which overpass the capabilities of common commercial circuit simulators. They use the symbolic computation of two simulation tools developed by our research team. The proposed algorithms are not limited by the operation behavior of the analyzed systems, being usable in both DC and AC circuits, as well as in transients. The developed method facilitates and speeds up the complex analyses required by repeated simulations specific to the modern design process. Three case studies are discussed to prove the efficiency of the developed algorithms. They cover real DC and AC applications, respectively. The results obtained using the Thévenin and Norton equivalent diagrams were validated through analyses of the initial systems.